Silibinin Suppresses Growth of Human Colorectal Carcinoma SW480 Cells in Culture and Xenograft through Down-regulation of β-Catenin-Dependent Signaling - Manjinder Kaur; Balaiya Velmurugan; Alpna Tyagi; Chapla Agarwal; Rana P. Singh; Rajesh Agarwal (Neoplasia: An International Journal for Oncology Research, 2010)
Mutations in APC/β-catenin resulting in an aberrant activation of Wnt/β-catenin pathway are common in colorectal cancer (CRC), suggesting that targeting the β-catenin pathway with chemopreventive/anticancer agents could be a potential translational approach to control CRC. Using human CRC cell lines harboring mutant (SW480) versus wildtype (HCT116) APC gene and alteration in β-catenin pathway, herein we performed both in vitro and in vivo studies to examine for the first time whether silibinin targets β-catenin pathway in its efficacy against CRC. Silibinin treatment inhibited cell growth, induced cell death, and decreased nuclear and cytoplasmic levels of β-catenin in SW480 but not in HCT116 cells, suggesting its selective effect on the β-catenin pathway and associated biologic responses. Other studies, therefore, were performed only in SW480 cells where silibinin significantly decreased β-catenin-dependent T-cell factor-4 (TCF-4) transcriptional activity and protein expression of β-catenin target genes such as c-Myc and cyclin D1. Silibinin also decreased cyclin-dependent kinase 8 (CDK8), a CRC oncoprotein that positively regulates β-catenin activity, and cyclin C expression. In a SW480 tumor xenograft study, 100- and 200-mg/kg doses of silibinin feeding for 6 weeks inhibited tumor growth by 26% to 46% (P < .001). Analyses of xenografts showed that similar to cell culture findings, silibinin decreases proliferation and expression of β-catenin, cyclin D1, c-Myc, and CDK8 but induces apoptosis in vivo. Together, these findings suggest that silibinin inhibits the growth of SW480 tumors carrying the mutant APC gene by down-regulating CDK8 and β-catenin signaling and, therefore, could be an effective agent against CRC.